The association between self-efficacy and self-care in essential hypertension: a systematic review - Tan, Felicia Clara Jun Hui; Oka, Prawira; Dambha-Miller, Hajira; Tan, Ngiap Chuan (BMC family practice, 2021)
The successful management of hypertension requires sustained engagement in self-care behaviour such as adhering to medication regimens and diet. Bandura's Social Cognitive Theory suggests that self-efficacy is a major determinant of engagement in self-care behaviour. Self-efficacy refers to an individual's belief in their capacity to execute behaviours necessary to produce specific performance attainments. This systematic review of observational studies aims to summarise and evaluate the quality of evidence available to support the association between self-efficacy and engagement in self-care behaviour in hypertension. Searches were performed of the Pubmed, MEDLINE, CINAHL and OpenSIGLE databases from database inception to January 2020. Reference lists and individual journals were also hand searched. Observational studies in English quantifying self-efficacy and self-care behaviour in hypertensive adults were included. The quality of included articles was assessed with the National Institute of Health Quality Assessment Tool for observational studies. The literature search identified 102 studies, of which 22 met the inclusion criteria for full-text review. There were 21 studies which reported that higher self-efficacy was associated with engagement in self-care behaviours including medication adherence (n = 9), physical activity (n = 2) and dietary changes (n = 1). Of these, 12 studies were rated as 'good' on the quality assessment tool and 10 were 'fair'. A common limitation in these studies was a lack of objectivity due to their reliance on self-reporting of engagement in self-care behaviour. Our review suggests an association between self-efficacy and self-care. However, the evidence supporting this association is of low to medium quality and is limited by heterogeneity. Our findings suggest the need for further well-designed interventional studies to investigate this association.